Percutaneous thrombin injection treatment of a femoral artery pseudoaneurysm with simultaneous arterial balloon occlusion: Case report and review of the literature - Onur Ergun; Pinar Celtikci; Idil Gunes Tatar; Metin Yilmaz; Baki Hekimoglu (KARE Publishing, 2016)
Iatrogenic femoral artery pseudoaneurysm at the level of the hip joint in a 52-year-old patient was treated by ultrasound-guided percutaneous thrombin injection, while a balloon was inflated at the neck of the pseudoaneurysm under fluoroscopy, to prevent thrombin leakage to the arterial system.